Limited effects of pre‐existing maternal antisocial behaviours on infant neurodevelopment: A pilot study. Issue 1 (7th July 2017) - Currie, Lisa; Pajer, Kathleen; Gardner, William; Cake, Heather; Shaw, Sarah; Patterson, Victoria
Abstract: Antisocial behaviour disorders (ABDs) are among the most costly and treatment resistant of all psychiatric syndromes. Select neurodevelopmental abnormalities have been labelled a risk factor for ABDs, but it is unknown if maternal ABDs are associated with early neurodevelopmental abnormalities. This study tested whether infants of ABD mothers had more neurodevelopmental abnormalities than mothers with no psychiatric disorder (ND). Thirty‐nine pregnant women (49% with ABDs; 51% no psychiatric disorder) were recruited from the community. Infant neurodevelopment was assessed at ≤1 and 8 weeks using the Neonatal Behavioural Assessment Scale and at 16 weeks of age using the Bayley Scales of Infant and Toddler Development‐III. There was no significant group difference at ≤8 weeks. At 16 weeks, ABD mothers rated their infants higher on the Adapted Behaviours subscale, specifically on the leisure and self‐directed scales, when corrected for substance use and socio‐economic status. This pilot study found higher maternal ratings of Adapted Behaviours at 16 weeks, which may be due to unrealistic expectations about infant development. Highlights: Maternal Antisocial behaviour disorders (ABDs) do not impact early infant neurodevelopment at ≤ 8 weeks old as measured by standardized assessment. Mothers with ABDs view their infants at 16 weeks as better adapted than women without any psychiatric disorder. Specifically, mothers with ABDs reported their infants as better adapted on the leisure and self‐direction subscales of the Bayley Scales of Infant and Toddler Development‐III. This finding may be due to less knowledge about normal infant adaptive behavior.